Effective Parameters onto Swelling Capacity of Biosuperabsorbent Based on Acrylonitrile-Sucrose - Soleimani, Fatemeh; Sadeghi, Mohammad; Shasevari, Hadis; Soleimani, Arezoo; Sadeghi, Hossein (Asian Journal of Chemistry, 2012)
After synthesis of a superabsorbent hydrogel based on sucrose and polyacrylonitrile, the effect of reaction variables such as concentration of NaOH and hydrolysis time and temperature were systematically optimized to achieve a hydrogel with swelling capacity as high as possible. Under the optimized conditions, maximum capacity of swelling in distilled water was found to be 610 g/g. Finally, the swelling kinetics of the hydrogels with various particle sizes was also investigated.